"...where they play, they become the sensation of the villages" / Romani theatre in Strážnice and its efforts for better perception of Roma - Slačka, Dušan; Viková, Lada (Romano džaniben, 2024)
The text presents the findings of a research project on a Romani theatre in south Moravian Strážnice from the 1930s to the 1950s. The study focuses on specific Romani figures involved in the theatre residing within two Romani communities in Strážnice and Petrov but also follows their ties with other Romani families in Radějov, Kněždub, Hrubá Vrbka, Tvarožná Lhota, Sudoměřice, and elsewhere. The article contextualises the emergence of the Romani theatre within the social and cultural conditions of the time, and analyses the limited surviving information on its functioning, main representatives and the themes of the plays staged. In doing so, it seeks to present the Romani theatre artists and the development of their activities in the context of their efforts to emancipate the Romani people, improve their position in society and liberate themselves from a marginalised position.